De-Radicalization of Intepretation the Concept of Nation and Jihad in Tafsir al-Azhar - Sidik Sidik (Analisa: Journal of Social Science and Religion, 2012)
There is no a single definition of state and jihad because there has been no agreement on the terms. Therefore, there is a gap between perceived concept of state and jihad and recent de- velopment of nation-state, plurality, and civility. In additions, the emergence of psychoso- cial factor such as truth claim and the feeling of being marginalized and oppressed results in radicalism under the banner of religion. Based on the aforementioned background, this paper seeks to discuss “Tafsir al-Azhar”, a monumental work of Haji Abdul Malik Karim Amrullah (Hamka), an Indonesian leading figure in tafsir (interpretation) study. This is the first tafsir book written in Bahasa Indonesia and becomes one of the main sources in the field. By using documentation and hermeneutics the writer revealed not only the substance and the method of interpreting the concepts of “state” and “jihad”, but also their significance for the attempt of de-radicalization in Indonesia. According to Hamka, the relationship between religion and state was integral and the formation of the state de- pended on social development; whereas the concept of jihad did not merely mean “war”. In a boarder meaning, the concept of jihad included physical and non-physical dimen- sions. Physical jihad (battle) was permissible under certain conditions and circumstances.